STRATEGI PEMASARAN PRODUK TABUNGAN BRITAMA PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK KANTOR CABANG BINTARO - Indri Damayanti; Erman Sutandar; Rosalina Ayudia (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2021)
Marketing is an institutional activity as a process for creating, communicating, delivering, and exchanging products or services that have value for customers, clients, partners, and society at large. The purpose of the study was to examine the right strategy in marketing the Britama savings product at PT. BRI (Persero) Tbk Bintaro Branch Office. This research is qualitative research with field study method and literature study. The results of the research are strategies that can be carried out to increase sales of Britama savings products, namely by using Personal Selling, Advertising, Publicity, Sales Promotion, Mass Selling, Merchant Cooperation Program Expansion, and Sponsorship & Exhibition strategies. The reason for combining these strategies is because BritAma's savings position is in the product life cycle, which is in the introduction stage